Competencies of secondary health education teacher in the division of city schools, Manila - Angeles, Pilar S. (s.n.], 1970)
The main concern of the study is finding out competencies of the secondary health education teachers in the Division of City Schools, Manila. It aims to know the present qualifications of health education teachers in the secondary schools in Manila and their professional competencies in terms of knowledge, skills, and attitudes in health services, instruction and healthful living of the health education teachers in the secondary schools in Manila. The study aims to serve as a baseline for designing in-service education programs slanted towards their professional needs and to help administrators, supervisors and department heads in determining the aspects of the teacher's work that need strengthening thus enabling them to teach effectively. Also, the study provides suggestions for enriching or improving the curriculum for teacher-preparation in health education.